The Influence of Work Enthusiasm on Employee Performance at CV. Super Inti Perkasa in Desa Amahusu, Kecamatan Nusaniwe, Kota Ambon - Christian, Elda Lie; Wairisal, Paulus Liberthy; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2024)
This study aims to analyze the influence of work enthusiasm on employee performance at CV. Super Inti Perkasa, a small and medium-sized enterprise located in Desa Amahusu, Kecamatan Nusaniwe, Kota Ambon. The research method used is quantitative, employing a survey technique with 36 respondents. The results show that work enthusiasm has a significant impact on employee performance, where employees with high work enthusiasm demonstrate better productivity, work quality, and job satisfaction. This study also highlights the importance of managerial support, a conducive work environment, and effective communication in enhancing work enthusiasm and employee performance. These findings are consistent with previous research indicating that work enthusiasm is a crucial factor in achieving optimal performance in small and medium-sized enterprises. The results are expected to serve as a reference for company management in designing more effective strategies to boost work enthusiasm and employee performance